2021
DOI: 10.1002/celc.202100891
|View full text |Cite
|
Sign up to set email alerts
|

Exposure History and its Effect Towards Stabilizing Li Exchange Across Disordered Rock Salt Interfaces

Abstract: The application of lithium rich disordered rock salts (DRX) as cathode materials has greatly expanded the materials space for high energy density cathodes. These materials are able to consistently achieve capacities higher than 250 mAhg À 1 via a complex percolation based intercalation mechanism. Most current DRX materials face significant capacity fade when cycled over an extended period. One of the factors responsible for this could be deleterious side effect of interface reactions between the electrode and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The broad and highly shifted resonance, which is itself composed of many broad and overlapping signals, corresponds to a distribution of paramagnetic Li environments in the DRX structure, as has been discussed in more detail in the previous work. [ 46–48 ] While the shape and intensity of the diamagnetic 7 Li signal do not evolve significantly upon cycling, the average chemical shift and linewidth of the broad resonance associated with Li in DRX structure changes during cycling in both electrolyte systems, but much more significantly for the E‐baseline. The 7 Li signal observed for LMTO cycled with E‐baseline is much reduced in intensity and significantly sharper than that observed for the pristine cathode, indicating a loss of Li inventory and a narrower distribution of Li chemical environments after cycling, consistent with local structural rearrangements and greater cation short‐range ordering in the bulk cathode after cycling.…”
Section: Resultsmentioning
confidence: 99%
“…The broad and highly shifted resonance, which is itself composed of many broad and overlapping signals, corresponds to a distribution of paramagnetic Li environments in the DRX structure, as has been discussed in more detail in the previous work. [ 46–48 ] While the shape and intensity of the diamagnetic 7 Li signal do not evolve significantly upon cycling, the average chemical shift and linewidth of the broad resonance associated with Li in DRX structure changes during cycling in both electrolyte systems, but much more significantly for the E‐baseline. The 7 Li signal observed for LMTO cycled with E‐baseline is much reduced in intensity and significantly sharper than that observed for the pristine cathode, indicating a loss of Li inventory and a narrower distribution of Li chemical environments after cycling, consistent with local structural rearrangements and greater cation short‐range ordering in the bulk cathode after cycling.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous reports have shown that manganese-rich (Mn-rich) cathodes suffer from Mn dissolution at high voltages which causes cathode active material loss, electrolyte decomposition, and surface reconstruction, thus leading to cell capacity decay. 21,22,23,24,25,26 The Mn species dissolved from the cathode can also migrate through the electrolyte and deposit on the anode surface. An optical image of the lithium metal anode and separator recovered from a cycled cell made with an LMO electrode (Figure S2) shows obvious black deposits at the surface, suggesting Mn dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in reversible capacity and discharge voltage upon washing leads to a significant increase in energy density, from 664 Wh/kg for LMTF25 to 744 Wh/kg for LMTF25w. Further analysis of the redox processes and associated structural changes is needed to determine whether the changes in the electrochemical behavior observed upon washing result from the removal of Li-containing impurities (mostly LiF and Li 2 O/LiOH) from the surface of the DRX particles or from a change in the surface structure of the DRX particles, as has been observed for other surface treatment processes applied to DRX and NMC-type cathodes. , Nevertheless, the present results are encouraging and indicate that washing DRX cathodes with water may be a viable process to improve electrochemical performance.…”
Section: Proposed Characterization Methodsmentioning
confidence: 99%